GEOMETRICALLY NON-LINEAR ANALYSIS OF SHELLS - ANDRZEJ AMBROZIAK (TASK Quarterly, 2006)
The work’s aim has been to verify the suitability of commercial engineering software for geometrically non-linear analysis of shell structures. The paper deals with static, geometrically non-linear analysis of shells made of isotropic materials. The Finite Element Method (FEM) has been chosen to solve the problem. The results of the ROBOBAT Robot Millennium v. 19.0 and MSC.Marc v. 2005r2 commercial software are compared with the literature results.